Penerapan Teaching Practic Seni Rupa pada Anak Usia Dini - Fadilla Mizratul Octavia; Aisyah Shinta Balqis; Juli Lestari; Seisky Seisky; Hilyatul Fauza; Ummi Khaira; Miranda Deswita; Ayu Citra Dewi (Institut Agama Islam Sumatera Barat, 2024)
This study aims to identify the role of art in early childhood learning, evaluate the effectiveness of the learning approach through play with art with the research theme